KERJASAMA GURU BK DAN GURU MATA PELAJARAN DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SMA NEGERI 1 TALAMAU KABUPATEN PASAMAN BARAT - Gusrita, Wilda - (Bimbingan dan Konseling, 2014)
Cooperation counselor and subject teachers are very important to increase learning students motivation because it can affect outcomes of students. However, there are still many students who are less motivation to learn. This research is descriptive qualitative research. Informants in this research are 2 couenselor, 2 math teachers, 2 english teachers, 2 indonesian teachers and 2 students as addition. Instrument of this research is interview and after that analiyze the data. Result of this study show that cooperation of counselor and subjek teachers to increase learning students motivation is done but it is not maximal. It seen from guiding students to use facilities efeetively less wells, and then guiding, students to know their personal to have prestations optimal is done, but it is not maximal. It can be concluded that cooperation of counselor and subject teachers to increase learning students mitivation at SMA Negeri 1 Talamau Pasaman Barat.